2019
DOI: 10.3390/plants8120594
|View full text |Cite
|
Sign up to set email alerts
|

Transgressivity in Key Functional Traits Rather Than Phenotypic Plasticity Promotes Stress Tolerance in A Hybrid Cordgrass

Abstract: Hybridization might promote offspring fitness via a greater tolerance to environmental stressors due to heterosis and higher levels of phenotypic plasticity. Thus, analyzing the phenotypic expression of hybrids provides an opportunity to elucidate further plant responses to environmental stress. In the case of coastal salt marshes, sea level rise subjects hybrids, and their parents, to longer tidal submergence and higher salinity. We analyzed the phenotypic expression patterns in the hybrid Spartina densiflora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Several authors have reported that hybridization during plant invasion may produce more adaptable hybrid species [ 4 , 5 , 36 ]. For example, the hybridization between the native species Spartina foliosa and the invasive species S. densiflora enhanced the adaptability of the hybrid species to salt and flooding stress [ 7 ]. In our previous research, the tolerance of Sphagneticola × guangdongensis to cadmium and drought stress was inconsistent with the tolerance of Sphagneticola × guangdongensis to flooding stress in this study [ 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have reported that hybridization during plant invasion may produce more adaptable hybrid species [ 4 , 5 , 36 ]. For example, the hybridization between the native species Spartina foliosa and the invasive species S. densiflora enhanced the adaptability of the hybrid species to salt and flooding stress [ 7 ]. In our previous research, the tolerance of Sphagneticola × guangdongensis to cadmium and drought stress was inconsistent with the tolerance of Sphagneticola × guangdongensis to flooding stress in this study [ 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…petiolaris [ 6 ]. Hybridization is particularly important under constantly changing environmental conditions [ 7 ]. Heterosis is the result of the non-additive phenotypic expression of one or more traits, which may be regulated by epigenetics and genetics.…”
Section: Introductionmentioning
confidence: 99%